Oral versus long-acting injectable antipsychotic in first episode schizophrenia: A 12 weeks interventional study - Ramandeep Kaur; Ajeet Sidana; Nidhi Malhotra; Shikha Tyagi (Indian Journal of Psychiatry)
Background: There is underutilization of long-acting injectable (LAI) antipsychotics for first-episode schizophrenia (FES) despite having convenient dosing and treatment retention. LAIs are predominantly used for patients with poor compliance, chronic course, and multiple relapses. Materials and Methods: Seventy-two treatment naïve patients with the first episode of Schizophrenia (DSM-5) were assessed for baseline severity of psychopathology using the positive and negative syndrome scale (PANSS) and quality of life (QOL) using the WHOQOL-BREF scale. Patients were randomized to receive either oral haloperidol or LAI haloperidol for a period of 12 weeks. Results: Both the groups had a significant reduction in PANSS scores and improvement in QoL over 12 weeks period (P = 0.0001). The LAI group showed greater adherence and significantly better quality of life than the oral group (P = 0.023). The mean numbers of side effects were less in the LAI group at week 2 as compared to the oral group. Conclusion: LAI haloperidol is similar to oral haloperidol in patients with FES with respect to treatment response and offers benefits in form of a lesser number of side effects during early treatment, overall better adherence rates, and better QOL.